(untitled) - R Krell (Rome, 1996)
The purpose of this bulletin is to distribute and make available information on the manufacturing, processing and marketing of value added bee products. It is directed at beekeepers as well as non-beekeepers, small entrepreneurs, extension officers and those involved in small business development. Therefore, it tries to provide enough information to understand the primary products and their present and potential use.
Keywords: bee culture,honeybee